Dry writing of highly conductive electrodes on papers by using silver nanoparticle–graphene hybrid pencils. Issue 2 (19th December 2016) - Park, Jun-Ho; Park, Myung-Joo; Lee, Jang-Sik
Abstract : The development of paper electronics would enable realization of extremely cheap devices for portable, disposable, and environmentally-benign electronics. Abstract : The development of paper electronics would enable realization of extremely cheap devices for portable, disposable, and environmentally-benign electronics. Here, we propose a simple dry-writing tool similar to a pencil, which can be used to draw electrically conducting lines on paper for use in paper-based electronic devices. The fabricated pencil is composed of silver nanoparticles decorated on graphene layers to construct layered hybrid nanostructures. This pencil can draw highly conductive lines that are flexible and foldable on conventional papers. Electrodes drawn using this pencil on conventional copy paper are stable during repetitive mechanical folding and highly resistant to moisture/chemicals. This pencil can draw a conductive line where its resistance can be tuned by changing the amount of nanoparticles. A nonvolatile memory device is realized on papers by hand written lines with different resistance. All memory elements are composed of carbons on papers, so complete data security can be achieved by burning the memory papers. This work will provide a new opportunity to fabricate electronic devices on real papers with good conductivity as well as robust mechanical/chemical stability.